1983
DOI: 10.1007/bf01299919
|View full text |Cite
|
Sign up to set email alerts
|

A monolayer culture of human gastric epithelial cells

Abstract: Our aim was to develop a fibroblast-free monolayer culture of human gastric mucosal cells, using the specimens obtained by routine endoscopic biopsy. Human gastric mucosa obtained from normal volunteers by endoscopic biopsy was dissociated from collagenase and hyaluronidase. Dissociated cells were cultured in supplemented Coon's modified Ham's F-12 medium. Within 24 hr of inoculation, the cells were attached to the culture dishes. This was followed by cellular outgrowth. On phase-contrast microscopy, all cells… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
23
0

Year Published

1988
1988
2018
2018

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 38 publications
(24 citation statements)
references
References 16 publications
1
23
0
Order By: Relevance
“…Using carcinogenic agents to induce the transformation of normal cells has been a routine method for the study of tumors in vitro (Male et al, 1987;Narayan et al, 2004). The isolation of normal, primary gastric epithelial cells, however, is not suitable for the study of carcinogenesis mechanisms as these cells rapidly enter into a senescence phase (Terano et al, 1983;Rutten et al, 1996;Smoot et al, 2000). In our previous study (Zhu et al, 2004a), we utilized telomerase reverse transcriptase (hTERT) and simian virus 40 (SV40) large T antigen to establish successfully a conditionally immortalized, normal human gastric epithelial cell line (NEC), which also expressed c-src/ Lyn kinase.…”
Section: Introductionmentioning
confidence: 99%
“…Using carcinogenic agents to induce the transformation of normal cells has been a routine method for the study of tumors in vitro (Male et al, 1987;Narayan et al, 2004). The isolation of normal, primary gastric epithelial cells, however, is not suitable for the study of carcinogenesis mechanisms as these cells rapidly enter into a senescence phase (Terano et al, 1983;Rutten et al, 1996;Smoot et al, 2000). In our previous study (Zhu et al, 2004a), we utilized telomerase reverse transcriptase (hTERT) and simian virus 40 (SV40) large T antigen to establish successfully a conditionally immortalized, normal human gastric epithelial cell line (NEC), which also expressed c-src/ Lyn kinase.…”
Section: Introductionmentioning
confidence: 99%
“…Histochemical study with succinate dehydrogenase activity identified 5% of cells as parietal cells, whereas immunohistochemical study with pepsinogen failed to reveal any chief cells (25). These cells possessed the capability to synthesize DNA as well as cyclic nucleotides (25,36), to produce and secrete mucous glycoprotein (25), and to generate prostaglandins (36).…”
Section: Resultsmentioning
confidence: 97%
“…The cells reached confluency on day 3. Over 90% ofthe cells were identified as mucous-producing epithelial cells (surface epithelial cells and mucous neck cells) by PAS staining and ultrastructural studies (25,35). Histochemical study with succinate dehydrogenase activity identified 5% of cells as parietal cells, whereas immunohistochemical study with pepsinogen failed to reveal any chief cells (25).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…have been successfully used to study cyto protection in vitro [2,3], Monolayer cultures of gastric mucous cells have also been pre pared from humans, either from biopsy or surgical specimens [4][5][6] but, to our knowl edge, they have not been used to study drug damage and protection of gastric epithelial cells in vitro.…”
mentioning
confidence: 99%